An Analysis Language Metaphor Found in “Twilight” Novel - Sitorus, Remida; Herman; Silalahi, Dumaris E.; Raja Sihombing, Partohap Saut (Global Science Independent Journal, 2020)
This research was conducted to analyze and find out the types of language metaphor and to find out the dominant of language metaphor found in “Twilight” novel. The researchers tried to answer two research questions, namely what are they kinds of language metaphor found in “Twilight” novel? What is the dominant of the types language metaphor found in “Twilight” novel? The theory used in this research is Richards in Madsar’s theory, where the theory discusses classifies the types of metaphor. This research was conducted using qualitative method with descriptive research design. This research is the text of novel and content analysis based on how to conduct qualitative research. Data collection procedures are observing, analyzed, classified, and reporting. The data is taken through the “Twilight” novel by Stephenie Meyer’s novel and take thirty-four page of the selected data. The data shows that the researchers found 45 expressions of metaphor. 11 or 24,44% metaphor are the Dead metaphor, 7 or 15,55% Extended metaphor, 5 or 11,11% Mixed metaphor, 18 or 40% Active metaphor, 4 or 8,88% Submerged metaphor in the novel “Twilight” by Stephenie Meyer’s novel. Finally, by knowing the result, the types of metaphor are found in “Twilight” novel, they are: dead metaphor, extended metaphor, mixed metaphor, active metaphor, and submerged metaphor, and the dominant metaphor in the novel “Twilight” by Stephenie Meyer’s novel is Active metaphor.